2008
DOI: 10.1016/j.biocon.2007.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of woodpasture on former agricultural land: The importance of safe sites and time gaps before grazing for tree seedlings

Abstract: Low intensity grazing Large herbivoresTree regeneration A B S T R A C TWoodpastures (open, grazed woodlands with a mosaic of grassland, shrub and tree patches) are of high biological and cultural value and have become a threatened ecosystem in Europe. Spontaneous tree regeneration in the presence of large herbivores, is an essential process for management and restoration of this structurally diverse habitat. We examined the suitability of five vegetation types (grasslands, ruderal vegetations, tall sedges, rus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 55 publications
0
48
1
3
Order By: Relevance
“…Other studies performed in different environments revealed that unpalatable shrub thickets play as shelters protecting woody species from browsing (Smit et al 2009;Van Uytvanck et al 2008;Vera 2000). However, the encroachment of juniper thickets may reduce the area where larch recruits more effectively and grows faster than late-successional species.…”
Section: Forest Structure and Grazing Pressurementioning
confidence: 97%
See 1 more Smart Citation
“…Other studies performed in different environments revealed that unpalatable shrub thickets play as shelters protecting woody species from browsing (Smit et al 2009;Van Uytvanck et al 2008;Vera 2000). However, the encroachment of juniper thickets may reduce the area where larch recruits more effectively and grows faster than late-successional species.…”
Section: Forest Structure and Grazing Pressurementioning
confidence: 97%
“…Mayer et al (2006) suggested to hold down a grazing pressure threshold of 1 LUּ ha -1 or to provide time intervals without grazing (Van Uytvanck et al 2008). Heavy grazing pressure followed by periods of moderate grazing is often associated to the onset of tree regeneration in many sites (Mast et al 1997).…”
Section: Forest Structure and Grazing Pressurementioning
confidence: 99%
“…Grazers are hypothesized to play a key role in this succession by damaging palatable tree saplings within grassland but not within spiny shrubs. Several empirical studies have indeed shown that unpalatable species-spiny or toxic plants-protect tree saplings from ungulate damage (Smit et al 2006a;Van Uytvanck et al 2008b), resulting in spatial associations between young palatable trees (e.g., pedunculate oak Quercus robur) and spiny or toxic plants (e.g., spiny blackthorn Prunus spinosa) (Bakker et al 2004;Smit et al 2005;Van Uytvanck et al 2008a). This process in which an unpalatable species facilitates a palatable species by reducing the amount of herbivory is called associational resistance (Hamback et al 2000;Milchunas and Noy-Meir 2002) and is considered an important factor in the proposed cyclic succession in grazed woodlands (Olff et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Deciduous trees, however, have a greater potential for compensatory growth (Hester et al 2004;Vandenberghe et al 2007). The browsing pressure on palatable seedlings may be lower if they are protected by surrounding unpalatable vegetation (Smit et al 2006;VanUytvanck et al 2008). Thorny or toxic shrubs may facilitate the survival of palatable trees, which in turn will grow and outshade the shrubs (Olff et al 1999;Bakker et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Thorny or toxic shrubs may facilitate the survival of palatable trees, which in turn will grow and outshade the shrubs (Olff et al 1999;Bakker et al 2004). Alternatively, time gaps (of a few years) in grazing can improve the growth of trees that regenerate abundantly in the absence of grazers (VanUytvanck et al 2008;VanUytvanck and Verheyen 2014).…”
Section: Introductionmentioning
confidence: 99%